Vitamin D deficiency in a population of migrant children: an Italian retrospective cross-sectional multicentric study. (9th October 2019) - Ceccarelli, Manuela; Chiappini, Elena; Arancio, Rosangela; Zaffaroni, Mauro; La Placa, Simona; D'Andrea, Marianna; de Waure, Chiara; Da Riol, Rosalia Maria; Valentini, Piero; ,
Abstract: Background: Vitamin D is a hot topic in the scientific community. Its deficiency and the implications for the children's health became increasingly discussed during the last 20 years. The main aim of this retrospective study was to determinate the prevalence of vitamin D metabolism disorders in a population of adopted children and their risk factors. Methods: We gathered data from 2140 children observed in five different National Working Group for the Migrant Children of the Italian Society of Pediatrics centers, variously located in Italy. Serum 25-hydroxy (OH)-D concentration was used to determine every child's vitamin D status, defined as severely deficient (serum 25-OH-D < 10 ng/ml), moderately deficient (serum 25-OH-D {≥10 ng/ml U < 20 ng/ml}), mildly deficient (serum 25-OH-D {≥20 ng/ml U < 30 ng/ml}) and normal (serum 25-OH-D ≥ 30 ng/ml). Results: Mean value of serum 25-OH-D was 22.7 ng/ml (SD ± 12.1). Vitamin D status was deemed as normal in 483 (22.6%) children, mildly deficient in 718 (33.6%) children, moderately deficient in 730 (34.1%) children and severely deficient in 209 (9.8%) children. Conclusions: A very high percentage of migrant children is affected by hypovitaminosis D, with a strong association with age, geographic origin, season of blood sample collection and time spent in Italy after the arrival. This finding highlights the need for corrective measures. However, these measures cannot be applied without increasing the access of migrant populations to healthcare services.